LAND CONSOLIDATION AND COOPERATIVES AS COMPONENTS OF CORPORATE GOVERNANCE IN AGRICULTURAL INDUSTRY (Third Sector Social Economic Review, 2018)
The major aim of this paper is to improve corporate governance by proposing different approaches and modeling techniques regarding the efficiency of resource allocation in Turkish agricultural industry and also to create awareness for stakeholders. The share of the agricultural industry in Turkish Economy, at first glance may seem low. However, given the linkage of the agricultural industry with the different sectors and the effects on the food industry, it can be said that agricultural industry has a ""strategic"" importance for the Turkish Economy. Considering the strategic importance, it becomes a necessity and crucial to improve infrastructure, business processes, and efficiency of this industry. In this respect, there is a room for improvement to increase the efficiency in allocation of agricultural resources within the framework of good governance approaches in such a global competitive business environment within the context of the current functioning of the agricultural industry in Turkey. In this study, model proposal is presented with the process of agricultural resource budget in mind in order to contribute to achieving the strategic aims and objectives in the agricultural industry, which is envisaged in the Medium Term Program (2018-2020). In this way, it is attempted to contribute to the literature and the practice.
Keywords: Corporate Governance; Agricultural Industry; Business Model; Land Consolidation; Cooperatives